THE CORRELATION BETWEEN THE STUDENTS’ READING HABITS AND ESSAY WRITING ABILITY - Nisa, Veni Lutfiya; Mabaroh, Barotun; Istiqomah, Dewi Masitho (Universitas Negeri Malang, 2023)
This study aims to find out whether there is a significant correlation between the students' reading habits and essay writing ability. The method used in this study is quantitative correlational research. The sample consisted of 39 students from the class of 2020 in the sixth semester of PGRI Wiranegara University. Data were collected using questionnaire and documentation instruments. The researchers analyzed the correlation by Pearson and Spearman formula by using IBM SPSS version 29. The findings revealed that the students were good at reading habits and essay writing ability. Beside that the researchers also found that the correlation between the two was low with the correlation coefficient was 0.334 and the significant value was 0.037. It can be concluded that there is a correlation between the students’ reading habits and essay writing ability.